Emphasized Mechanistic Antimicrobial Study of Biofunctionalized Silver Nanoparticles on Model Proteus mirabilis - Parveen, Asra (J Drug Deliv, 2018)
Antimicrobial study of biofunctionalized silver nanoparticles has been done with the emphasis on its mechanism on both gram positive and negative bacteria. The biofunctionalized silver nanoparticles are employed considering their importance in green chemistry with respect to easy synthesis, usefulness, and economic synthetic procedure involved. The stability of these nanoparticles was determined by zeta potential analyzer. The probable mechanism of antibacterial activity was performed on Proteus mirabilis by field emission scanning electron microscopy (FESEM) and energy dispersive spectroscopy (EDAX) study which does not show the presence of silver. The free radicals generated by silver nanoparticles were responsible for lethal antibacterial activity by rupturing the cell surface which causes improper nutrient and signal supply. Free radical scavenging efficacy of silver nanoparticles was confirmed by 1,1-Diphenyl-2-picrylhydrazyl (DPPH) method. AgNP enhanced the membrane leakage of reducing sugars by destroying the proteins existing on the cell wall. These nanoparticles are found to be toxic against human pathogens and are highly effective on Staphylococcus aureus. The effect of silver nanoparticles is concentration dependent and independent of the type of strains used.